IIUM tracer study 2016 follow up - Isa, Khadijah; Wok, Saodah; Rokis, Rohaiza; Abdul Rahman, Shukran; Zubairi, Ainol Madziah; Md Ghalib, Mohd. Feham; Tunku Mohd Mokhtar, Tunku Mohar; Zul Kepli, Mohd Yazid; Wan Husain, Wan Rohaida; Sulaiman, Muhammad Karimi (Alumni and Global Networking Division, 2017)
The IIUM Tracer Study 2016: Follow Up is the third report of the Tracer Study 2016 project conducted by the International Islamic University Malaysia (IIUM) under the purview of the Alumni and Global Network Division (AGND). This project is a substantial initiative and effort by AGND that receives a strong support from the University to publish a well comprehensive quantitative data report about IIUM’s graduates in collaboration with the Ministry of Higher Education (MOHE). The objective of the survey is to update the employment status of IIUM graduates (Class of 2016). The data was collection 6-months after their graduation (May – October 2017). A total of 4,481 graduates participated in the study, involving 3,815 First Degree graduates and 666 Postgraduate. The respondents for the study were the graduates of the 32nd IIUM Convocation. They include; 1. Ahmad Ibrahim Kulliyyah of Laws (AIKOL), 2. IIUM Institute of Islamic Banking and Finance (IIiBF), 3. International Institute of Islamic Thought and Civilisation (ISTAC), 4. International Institute for Halal Research and Training (INHART) 5. Kulliyyah of Allied Health Science (KAHS), 6. Kulliyyah of Architecture and Environmental Design (KAED), 7. Kulliyyah of Dentistry (KOD), 8. Kulliyyah of Engineering (KOE), 9. Kulliyyah of Economics and Management (KENMS), 10. Kulliyyah of Education (KOED), 11. Kulliyyah of Information and Communication Technology (KICT), 12. Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), 13. Kulliyyah of Language and Management (KLM) 14. Kulliyyah of Medicine (KOM), 15. Kulliyyah of Nursing (KON), 16. Kulliyyah of Pharmacy (KOP), and 17. Kulliyyah of Science (KOS). Given that the Tracer Study series have yielded important employment related findings and facts that provide useful information to the University in particular and the nation in general, it is hoped that this particular Report will continue to provide useful, comprehensive and exhaustive information to all, particularly to IIUM and MOHE.